Online Ratings and Reviews of American Orthopaedic Foot and Ankle Surgeons. Issue 1 (February 2020) - Velasco, Brian T.; Chien, Bonnie; Kwon, John Y.; Miller, Christopher P.
Background. Utilization of physician rating websites continues to expand. There is limited information on how these websites function and influence patient perception and physicians' practices. No study to our knowledge has investigated online ratings and comments of orthopaedic foot and ankle surgeons. We identified factors impacting online ratings and comments for this subset of surgeons.Methods. 210 orthopaedic foot and ankle surgeons were selected from the American Orthopaedic Foot and Ankle Society (AOFAS) website. Demographic information, ratings, and comments were reviewed on the 3 most visited public domain physician ratings websites:HealthGrades.com, Vitals.com, and Ratemds.com. Content differences between positive and negative comments were evaluated.Results. The mean review rating of 4.03 ± 0.57 out of 5 stars. 84% of the total number of ratings were either 1 star (17%) or 5 stars (67%). Most positive comments related to outcome, physician personality, and communication, whereas most negative comments related to outcome, bedside manner, and waiting time. χ 2 Analyses revealed statistically significant proportions of positive comments pertaining to surgeon-dependent factors (eg, physician personality, knowledge, skills) and negative comments concerning surgeon-independent factors (eg, waiting time, logistics).Conclusion. This study examined online ratings and written comments of orthopaedic foot and ankle surgeons. Surgeons had a generally favorable rating and were likely to have positive comments. Patients were likely to write positive comments about surgeon personality and communication, and negative comments pertaining to bedside manner and waiting time. Knowledge and management of online content may allow surgeons to improve patient satisfaction and online ratings. Level of Evidence: Level IV